Học tập trải trong chuyên ngành đạo diễn sự kiện qua môn học tổ chức sự kiện cho sinh viên Trường Đại học Văn hóa Hà Nội - Nguyễn, Thị Thanh Bình (Hiệp hội thiết bị giáo dục Việt Nam, 2023)
Along with the development of society, the demand for employees is increasing. Human resources need to have good quality, professional qualifications, the ability to do practical jobs, and at the same time need to be highly adaptableThis is a challenge for educators, because besides learning theory, training students to be able to adapt to real work is also a high requirement. Hanoi University of Culture is a university with many subjects to be learned in the form of experience, event organization is one of those subjectsThe article presents some theories about experiential learning, and also describes the experiential learning process in the event organization subject at school.